2003
DOI: 10.1161/01.hyp.0000097549.70134.d8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium Loading Increases Arterial Pressure in Afferent Renal–Denervated Rats

Abstract: Abstract-In rats fed high sodium diet, increasing renal pelvic pressure Ն3 mm Hg activates renal mechanosensory nerves, resulting in a renorenal reflex-induced increase in urinary sodium excretion. The low activation threshold of the renal mechanosensory nerves suggests a role for natriuretic renorenal reflexes in the regulation of arterial pressure and sodium balance. If so, interruption of the afferent renal innervation by dorsal rhizotomy (DRX) at T 9 -L 1 would impair urinary sodium excretion and/or increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 46 publications
6
43
0
Order By: Relevance
“…18 -21 It is conceivable that a defect in the sensory nervous system may lead to hypertension associated with reduced sodium excretion. Indeed, sodium excretion in response to sodium loading is impaired in salt-sensitive hypertension induced by sensory nerve degeneration of neonatally capsaicin-treated rats or surgically denervated rats, 3,[22][23][24] as well as in DS rats. [25][26][27] Therefore, the susceptibility of DS rats to hypertension may be attributed, at least in part, to the lack of adequate counterregulatory action of sensory nerves, and the resistance to hypertension in DR rats may be related to an enhanced function of sensory nerves.…”
Section: Wang and Wang Trpv1 Receptor And Dahl Salt Hypertensionmentioning
confidence: 99%
“…18 -21 It is conceivable that a defect in the sensory nervous system may lead to hypertension associated with reduced sodium excretion. Indeed, sodium excretion in response to sodium loading is impaired in salt-sensitive hypertension induced by sensory nerve degeneration of neonatally capsaicin-treated rats or surgically denervated rats, 3,[22][23][24] as well as in DS rats. [25][26][27] Therefore, the susceptibility of DS rats to hypertension may be attributed, at least in part, to the lack of adequate counterregulatory action of sensory nerves, and the resistance to hypertension in DR rats may be related to an enhanced function of sensory nerves.…”
Section: Wang and Wang Trpv1 Receptor And Dahl Salt Hypertensionmentioning
confidence: 99%
“…In contrast, renal afferent nerves were described to act protectively against salt-sensitive hypertension and the structural renal damage of high blood pressure (24,44). A more recent study using a more selective method of renal afferent denervation suggests that this might not be the case, but it could be shown that selective renal afferent denervation was able to blunt the development of deoxycorticosterone acetate-salt hypertension (12).…”
mentioning
confidence: 99%
“…Clinical reports on patients after thermal ablation point to an independent role of afferent renal innervation on blood pressure (33). Experimental data suggest that renal afferent denervation may be protective against the development of high blood pressure (26,42) as well as the progression of renal structural damage in renal disease (6,43). Hence, nonselective thermal ablation of afferent renal nerves in resistant human hypertension may not be always beneficial since the exact pathophysiological situation is normally not well defined (27).…”
mentioning
confidence: 99%